2014
DOI: 10.1007/s10072-014-1717-5
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction can improve learning ability in C57/BL mice via regulation of the insulin-PI3K/Akt signaling pathway

Abstract: To identify the molecular mechanism underlying improved spatial learning ability of C57/BL mice on a caloric restricted (CR) diet. Seven-week-old male C57/BL mice were randomly divided into three groups: normal control group (NC group, n = 10), high energy group (n = 10), and low energy group (CR group, n = 10). Body mass and levels of blood glucose were measured every 2 weeks over the course of 30 weeks. After 30 weeks, metabolic parameters, serum total cholesterol, and insulin-like growth factor 1 (IGF-1) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…Abundant evidence shows that CR increases the life span in several model organisms, ranging from yeast to mice and even primates. Earlier research has demonstrated that CR ameliorates age-related cognitive deficits, consistent with our recent findings [15,40]. CR has been shown to efficiently stimulate autophagy in vivo and in vitro [41].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Abundant evidence shows that CR increases the life span in several model organisms, ranging from yeast to mice and even primates. Earlier research has demonstrated that CR ameliorates age-related cognitive deficits, consistent with our recent findings [15,40]. CR has been shown to efficiently stimulate autophagy in vivo and in vitro [41].…”
Section: Discussionsupporting
confidence: 88%
“…Diets were purchased from the Experimental Animal Center of the Academy of Military Medical Sciences. The energy ratio of the diets fed to the NC, CR, and HC groups was 1:0.7:1.3 [15]. Mice were weighed monthly.…”
Section: Animals and Dietmentioning
confidence: 99%
“…Dementia prevalence is increasing with rapid aging in the population, and MCI as an intervention stage to prevent dementia has become a research hotspot [12,13]. Most recent studies have focused on the role of IR as possible links between diabetes and AD, and the disturbances in brain insulin signaling mechanisms may contribute to the molecular, biochemical, and histopathological lesions in AD [1,14]. Therefore, in this paper, how IR and cognitive impairment are mutually linked and the possible mechanisms are discussed.…”
Section: Introductionmentioning
confidence: 93%
“…In the aging rat brain, CR improved ketone body metabolism and blood flow, often impaired in neurodegenerative disorders . CR also delayed neurodegeneration in aging mice through SIRT1 (Graff et al 2013), improved learning through PI3k/Akt pathway (Ma et al 2014) and was demonstrated to attenuate amyloid b neuropathology in aged mice with Alzheimer's disease (Wang et al 2005). Finally, one of the few investigation conducted in humans showed that a 3-month CR intervention improved memory in the elderly (Witte et al 2009).…”
Section: Caloric Restrictionmentioning
confidence: 98%